2006
DOI: 10.1038/ng1726
|View full text |Cite
|
Sign up to set email alerts
|

The sex-specific genetic architecture of quantitative traits in humans

Abstract: Mapping genetically complex traits remains one of the greatest challenges in human genetics today. In particular, gene-environment and gene-gene interactions, genetic heterogeneity and incomplete penetrance make thorough genetic dissection of complex traits difficult, if not impossible. Sex could be considered an environmental factor that can modify both penetrance and expressivity of a wide variety of traits. Sex is easily determined and has measurable effects on recognizable morphology; neurobiological circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
287
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(313 citation statements)
references
References 28 publications
23
287
1
2
Order By: Relevance
“…Our results of no sex-specific genetic effects for BMI are in agreement with some family studies [18,19], but they are in contrast with twin studies that found higher [2,3,13,14], or lower [15][16][17] heritability estimates in women than in men. Schousboe et al [6] found slight differences between women and men in the extent of additive genetic and common environmental influences on BMI, anthropometric measures of fat distribution and fat% and LMI estimated by bioelectrical impedance in twins, but CIs were broad and overlapped for most estimates.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results of no sex-specific genetic effects for BMI are in agreement with some family studies [18,19], but they are in contrast with twin studies that found higher [2,3,13,14], or lower [15][16][17] heritability estimates in women than in men. Schousboe et al [6] found slight differences between women and men in the extent of additive genetic and common environmental influences on BMI, anthropometric measures of fat distribution and fat% and LMI estimated by bioelectrical impedance in twins, but CIs were broad and overlapped for most estimates.…”
Section: Discussionsupporting
confidence: 90%
“…Studies on sex differences in heritability of BMI have shown inconsistent results. Some studies found evidence for a higher heritability of BMI in women than in men [2,3,[12][13][14] or the other way around [15][16][17] or no difference [18,19]. In the Diabetes Heart Study [7], heritability estimates were larger in women for BMI and lean mass but not for fat percentage (fat%) assessed by dual-energy x-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 99%
“…mB Megabase *Genetic positions of markers showing the strongest evidence of linkage to lipid variables and 95% CIs were obtained from our high-density reference rat linkage map constructed in a GK×BN cross [13]. **Data derived following the integration of the rat genetic map in the rat genome sequence and comparative genome analyses (http://www.well.ox.ac.uk/rat_mapping_resources) [34]. We only report physical distances in the rat, mouse and human genomes (http://www.ensembl.org/Rattus_norvegicus/) for the 95% CI intervals of the most significant QTL.…”
Section: Discussionmentioning
confidence: 99%
“…The aims were to quantify the relative roles of additive genetic and shared household effects in determining faecal egg counts of N. americanus and, given recent reports of sex-differences in heritabilities of a broad range of quantitative traits in humans (Weiss et al 2006), to explore the relative role of both factors in males and females.…”
mentioning
confidence: 99%